The Effect of Value Added Tax and Sales Tax Incentives on Luxury Goods on Consumer Purchasing Power - Hermanto, Hermanto (CV. Strata Persada Academia, 2023)
The research we conducted here was motivated by various problems related to the purchasing power of motor vehicle consumers regarding Value Added Tax (VAT) and Sales Tax Incentives for Luxury Goods (PPnBM). This research was designed to determine consumer purchasing power. Value Added Tax (VAT) and Sales Tax Incentives for Luxury Goods (PPnBM) on motorized vehicles. The method used in this research is quantitative with the sample determination method, namely the Probability Method. This method is a method that uses area sampling and uses a purposive sampling method. The research results we obtained show that simultaneously, Value Added Tax (VAT) and Sales Tax Incentives on Luxury Goods (PPnBM) have a significant effect on the purchasing power of motor vehicle consumers. Partially Value Added Tax (VAT) significantly effects motor vehicle consumers' purchasing power. At the same time, the Sales Tax Incentive on Luxury Goods (PPnBM) PPnBM significantly affects the purchasing power of motor vehicle consumers.